INDIAN SCROLL PAINTINGS AS ILLUSTRATIONS - Sharma, Namrita; Rani, Pallavi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Scroll paintings have been an integral part of India’s visual and oral storytelling tradition. It is the variations as well as certain similarities in the visual devices used in the scrolls across traditions which makes them unique till date as indigenous. With the diminishing practice of these paintings due to various factors, its inclusion into the mainstream creative industry practice as well as understanding the indigenous visual practice becomes essential. In the currently existing scholarship, these paintings have been analyzed from the perspectives of heritage preservation, their narrative qualities, context, aesthetics however, its illustrative character mapping and its application in design education to enrich the knowledge of visual design gamut requires further exploration. This study attempts to address the understanding of the compositional character of these scrolls for common patterns or design by identifying the methods of arranging the visual elements i.e. the modes of composition.